Atenção pré-natal na cidade de Pelotas, Rio Grande do Sul, Brasil Prenatal care in the city of Pelotas, in the State of Rio Grande do Sul, Brazil - Isabel Cristina Rosa Barros Rasia; Elaine Albernaz (Instituto Materno Infantil de Pernambuco, 2008)
OBJETIVOS: identificar as características da assistência pré-natal na da cidade de Pelotas, Rio Grande do Sul, Brasil. MÉTODOS: estudo transversal aninhado a uma coorte de 2741 mães, entrevistadas nas maternidades da cidade, no período de setembro de 2002 a maio de 2003. As pacientes incluídas responderam a um questionário padronizado que obteve dados referentes a fatores demográficos e socioeconômicos e características do pré-natal. O desfecho analisado foi pré-natal adequado ou inadequado conforme o número de consultas, sendo definido como adequado, a realização de seis ou mais consultas. RESULTADOS: observou-se que 77% das gestantes fizeram seis ou mais consultas de pré-natal, porém, existem falhas no cumprimento e no manejo das normas de assistência pré-natal, como tratamento de problemas ginecológicos e orientações educativas. O risco de não realizar um pré-natal adequado foi maior para as gestantes de cor negra ou parda (RO=1,7), com menor escolaridade (RO=3,3) e menor renda (RO=3,0); assim como para as gestantes sem companheiro (RO=2,0) e fumantes (RO=1,5). CONCLUSÕES: os resultados condizem com os achados na literatura, na qual existe uma inversão de cuidados. As pacientes com piores condições econômicas e pouca escolaridade apresentam um maior risco para a realização de um pré-natal inadequado e suas conseqüências. OBJECTIVES: to identify key features of prenatal care in the city of Pelotas, in the State of Rio Grande do Sul, Brazil. METHODS: a cross-sectional study was conducted with a cohort of 2741 mothers, interviewed in the city's clinics, between September 2002 and May 2003. The mothers included answered a standard questionnaire which provided data regarding demographic and socioeconomic factors as well as aspects relating to prenatal care and the clinics attended. The outcome was considered to be either proper or improper prenatal care, the criterion being the number of medical consultations, with six or more appointments constituting adequate prenatal care. RESULTS: it was observed that 77% of the expectant mothers carried out six or more prenatal consultations, but there were shortcomings in terms of the success and management of prenatal care, such as treatment of gynecological problems and education. The risk of not having proper prenatal care was higher among black or mixed-race expectant mothers (RO=1.7), with fewer years of schooling (RO=3.3) and lower income (RO=3.0). This was also the case with expectant mothers without partners (RO=2.0), and smokers (RO=1.5). CONCLUSIONS: the results are consistent with those found in the literature, which depict an inversion of the needed pattern of care. Patients with the worse economic conditions and the least schooling, run a higher risk of receiving inadequate prenatal care and of being subject to the consequences of this.